JENIS DAN PERSENTASE PARASITOID TELUR HAMA PENGGULUNG DAUN PISANG (Erionata thrax L) (LEPIDOPTERA: HESPERIIDAE) PADA BEBERAPA KETINGGIAN TEMPAT DI KABUPATEN MINAHASA - Melisa Catrina Paath; Jantje Pelealu; R. M. Meray (Universitas Sam Ratulangi, 2018)
ABSTRACT. Melisa, Jantje Pelealu, and Elisabeth Meray. 2019. Species and Percentage of Parasitoid of Banana Leaves (Erionata thrax L) (Lepidoptera: Hesperiidae) at Several Altitude Places in Minahasa District. The aim of the study was to determine the type and percentage of Erionata thrax egg parasitoid at several altitudes in Minahasa Regency, namely the height of 0-100 meters above sea level in the Village of Kalasey, 101-200 mdpl Sea, and 201 - 300 masl Warembungan. The study lasted for four months, namely April 2016 to July 2016. The experiment used the survey method. Determination of sampling is done by drawing diagonal lines in the location. Each diagonal point is defined as five clumps of banana plants for sampling. Sampling was taken randomly in five clumps of banana plants. Data collection is done once a month. The way to take samples is to take as many eggs as E. thrax found on the lower surface of the leaves. The parasitoid that comes out of the egg is separated and included in killing bottle. The percentage of parasitic eggs is done by counting the number of parasitic eggs. The results showed that there were types of parasitoid, namely Agiommatus sumatraensi, Anastatus sp., Pediobius erionotae, and Ooencyrtus pallidipes. Total Parasitization of egg parasitoid of E. thrax pests at an altitude of 0 - 300 masl in Minahasa District reached 68.5%. The highest paritation, namely P. erionatae, reached 19.1%. Keywords : Parasitoid in the eggs, E. thrax, different altitudes